Mould spoilage of foods and beverages: Using the right methodology. (August 2019) - Rico-Munoz, Emilia; Samson, Robert A.; Houbraken, Jos
Abstract: Fungal spoilage of products manufactured by the food and beverage industry imposes significant annual global revenue losses. Mould spoilage can also be a food safety issue due to the production of mycotoxins by these moulds. To prevent mould spoilage, it is essential that the associated mycobiota be adequately isolated and accurately identified. The main fungal groups associated with spoilage are the xerophilic, heat-resistant, preservative-resistant, anaerobic and psychrophilic fungi. To assess mould spoilage, the appropriate methodology and media must be used. While classic mycological detection methods can detect a broad range of fungi using well validated protocols, they are time consuming and results can take days or even weeks. New molecular detection methods are faster but require good DNA isolation techniques, expensive equipment and may detect viable and non-viable fungi that probably will not spoil a specific product. Although there is no complete and easy method for the detection of fungi in food it is important to be aware of the limitation of the methodology. More research is needed on the development of methods of detection and identification that are both faster and highly sensitive. Highlights: To prevent mould spoilage, knowledge of the associated mycobiota is essential. To assess mould spoilage, the right methodology to detect the associated mycobiota must be used. Both classical and molecular methods have advantages and disadvantages. It is important to be aware of the limitations of the methodology. Methods of detection and identification that are both faster and highly sensitive are needed.